Use of wearable sensors to assess patterns of trunk flexion in young and old workers in the Metalworking Industry - Porta, Micaela; Orrù, Pier Francesco; Pau, Massimiliano (Ergonomics, 2021)
Workers exposed to repeated trunk flexions are at risk of onset of low-back disorders and in individuals aged over 50 this issue is exacerbated by the physiologic decline of the musculoskeletal system and longer lifetime occupational exposure. In this study, we investigated the existence of possible age-related differences in patterns of trunk flexion of workers in the metalworking industry. Thirty-three subjects were monitored during an actual shift using a wearable Inertial Measurement Unit (IMU) to assess trunk flexion angles (i.e. between 30° and 60°, 60°-90° and > 90°). Results show that older workers spent less time with their trunk flexed, regardless of the class of flexion considered, with respect to their younger colleagues. Although further studies are necessary to clarify the existence of strategies aimed at optimising trunk movements during ageing, the IMU-based approach appears useful in highlighting potentially harmful conditions, especially in workers with marked signs of decline in their physical capacities. Practitioner summary: Wearable sensors, which are well tolerated and minimally intrusive, represent a valid option to continuously monitor trunk posture in workers employed in metalworking industry. The results of this study show that they provide valuable information about the patterns of flexion of young and old individuals engaged in physically demanding tasks.